Pengaruh Laba Akuntansi, Arus Kas dan Ukuran Perusahaan Terhadap Return Saham Pada Perusahaan Transportasi dan Logistik yang Terdaftar di BEI - Ramasyakia Putri, Elisa; Wardatul Afiqoh, Nyimas (Journal of Culture Accounting and Auditing, 2025)
This research aims to examine accounting profits, operating cash flows, investment cash flows, funding cash flows and company size on stock returns in transportation and logistics companies listed on the Indonesia Stock Exchange. This type of research uses a quantitative approach. The sampling technique in this research was purposive sampling which produced 30 samples of transportation and logistics companies listed on the Indonesia Stock Exchange 2021-2023. Assisted by the IBM SPSS version 27 measuring tool. The results of the research show that accounting profit, operating cash flow, investment cash flow and funding cash flow have a positive effect on stock returns in transportation and logistics companies. Company size has no effect on stock returns in transportation and logistics companies.